2020
DOI: 10.3390/su12062338
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Bacterial Community, Root-Soil Interaction and Tomato Yield to Different Practices in Subsurface Drip Irrigation

Abstract: The objective of this study was to reveal the regulatory mechanisms underlying the soil bacterial community of subsurface drip irrigation (SDI). The effect of different buried depths of drip tape (0, 10, 20, 30 cm) on the soil bacterial community in a tomato root-zone was investigated using high-throughput technology. Furthermore, the mutual effects of root growth, tomato yield and soil bacterial community were also analyzed to explore the response of root-soil interaction to the buried depth of drip tape. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results revealed that fertilization and irrigation greatly increased bacterial diversity in the soil; meanwhile, irrigation specifically increased the richness of soil bacteria (Figure 1C). Previous research has demonstrated that changes in soil moisture levels can directly and indirectly influence bacterial abundance and community composition [49]. Specifically, irrigation has been found to enhance nutrient availability, create a fluctuation between dry and wet soil conditions, and promote the proliferation of soil bacteria [50].…”
Section: Effect Of Irrigation and Fertilization On Soil Bacterial Com...mentioning
confidence: 99%
“…The results revealed that fertilization and irrigation greatly increased bacterial diversity in the soil; meanwhile, irrigation specifically increased the richness of soil bacteria (Figure 1C). Previous research has demonstrated that changes in soil moisture levels can directly and indirectly influence bacterial abundance and community composition [49]. Specifically, irrigation has been found to enhance nutrient availability, create a fluctuation between dry and wet soil conditions, and promote the proliferation of soil bacteria [50].…”
Section: Effect Of Irrigation and Fertilization On Soil Bacterial Com...mentioning
confidence: 99%
“…The variation of soil moisture, can directly or indirectly affect soil bacterial abundance, and community structure. Furthermore, the soil moisture distribution in different buried depths of drip tape can also differentiate root growth and therefore regulates and controls the interaction between root growth and the soil bacteria community ( Wang, Li & Niu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%